PENGARUH RISIKO KREDIT, RISIKO PASAR, RISIKO LIKUIDITAS, DAN RISIKO MODAL TERHADAP RETURN SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING - Dhynandra Windasari; Agus Purwanto (Diponegoro Journal of Accounting, 2020)
This research aims to examine the effect of credit risk, market risk, liquidity risk, and capital risk to stock return using firm size as moderating variable. credit risk, market risk, and liquidity risk are independent variables. Dependent variable of this research is stock return. Moderating variable that used in this research is firm size. The population of this research consisted of banks listed on Indonesia Stock Exchange for the period 2013-2017. The sampling using purposive sampling method and the final sample is 141 samples. This research used multiple regression analysis and moderated regression analysis (MRA) by absolute residual value for test hypotheses. The research result reveals that credit risk, and capital risk were not affecting on stock return. Meanwhile, market risk and liquidity risk negatively affected on stock return. In addition, firm size can moderated the effect of market risk on stock return, but cannot moderate the effect of credit risk, liquidity risk and capital risk on stock return.